Arka White and Arka Pink: Novel Gerbera hybrids - Aswath, C; Kumar, Rajiv (Indian Horticulture, 2020)
Novel gerbera hybrids, viz. Arka White and Arka Pink were developed through hybridization using half-sib method of breeding where improved line/hybrid, IIHR9 and Arka Ashwa, were crossed with pollen mixed from different varieties. These hybrids were evaluated for flower quality traits for two years under naturallyventilated polyhouse. The Arka White (White group, NN155A) and Arka Pink (Red purple group, 65A) have novel flower colour with semi-double and double type of flowers, respectively. These hybrids are suitable for cut-flower and flower arrangement purposes. These hybrids will prove useful for developing more gerbera hybrids with novel traits.